2019
DOI: 10.1128/jcm.00674-19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Empiric β-Lactam Susceptibility Prediction among Enterobacteriaceae by Molecular β-Lactamase Gene Testing

Abstract: The use of rapid diagnostic tests (RDTs) for blood cultures has become standard of care in the United States to inform early antimicrobial optimization. The relative ability of genotypic and phenotypic approaches to identify beta-lactam susceptibility in Escherichia coli, Klebsiella spp., and Proteus mirabilis was evaluated, using incidence rates of resistance mechanisms to third-generation cephalosporins, aztreonam, and piperacillin-tazobactam seen across U.S. census regions. Overall, the presence of CTX-M, K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…The decision to alter antimicrobial therapy was based on clinical guidelines, so mainly exploited results from two of the 20 organism targets and only two resistance markers, mecA and carbapenemase enzymes; it is possible that the negative predictive value for the detection of phenotypic resistance could be lower depending on prevalence of non-panel resistance mechanisms. ( Spafford et al, 2019 ) Whether these potential false-negative and false-positive molecular results will degrade the utility of the assay awaits a prospective interventional study performed at multiple sites. The exclusion of expectorated sputum from the analysis may also have increased the specificity of the test for pathogens causing true disease.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to alter antimicrobial therapy was based on clinical guidelines, so mainly exploited results from two of the 20 organism targets and only two resistance markers, mecA and carbapenemase enzymes; it is possible that the negative predictive value for the detection of phenotypic resistance could be lower depending on prevalence of non-panel resistance mechanisms. ( Spafford et al, 2019 ) Whether these potential false-negative and false-positive molecular results will degrade the utility of the assay awaits a prospective interventional study performed at multiple sites. The exclusion of expectorated sputum from the analysis may also have increased the specificity of the test for pathogens causing true disease.…”
Section: Discussionmentioning
confidence: 99%
“…and P. mirabilis isolates from 72 US hospitals in 2012 found that 87% of isolates with ceftriaxone MICs ≥2 mg/L carried bla CTX-M genes, 7% ampC genes, and 6% had only narrow-spectrum β-lactamase genes. 2 Another US study including 482 E. coli , Klebsiella spp. and P. mirabilis ceftriaxone-non-susceptible isolates from 2014–15 found that ESBL genes (including bla CTX-M and ESBL variants of bla SHV and bla TEM ) were identified in 64% of isolates, p- ampC genes in 0.5% of isolates, both ESBL and p- ampC genes in 13% of isolates, and narrow-spectrum β-lactamase genes alone were identified in 22% of the 376 organisms.…”
Section: Using Ceftriaxone Non-susceptibility As a Proxy For Esbl Production Is Inaccuratementioning
confidence: 99%
“…The problems are illustrated in an exchange between Spafford et al. ( Spafford et al., 2019 ; Humphries et al., 2020 ) and Pogue and Heil (2020) , regarding the use of genotypic tests for bla CTX-M , bla KPC , and bla NDM in blood culture panels to predict phenotypic resistance or susceptibility to extended-spectrum cephalosporins and carbapenems in gram-negative organisms. The high very major error rates (which indicate false susceptibility to an antimicrobial agent) and variable negative predictive values of the molecular tests by geographic region and hospital type, led Spafford et al.…”
Section: Molecular Tests To Identify Resistance Genes In Positive Blood Culture Bottles and Respiratory Specimensmentioning
confidence: 99%